IMPLEMENTATION OF DELETION OF VEHICLE NUMBERS OF UNREGISTERED TAXPAYERS AFTER THE VALID PERIOD OF THE VEHICLE NUMBER REGISTRATION CERTIFICATE EXPIRES IN PEKANBARU CITY BASED ON LAW NUMBER 22 OF 2009 CONCERNING ROAD TRAFFIC AND TRANSPORTATION - Tarigan, Dwi Franata; Asnawi, Eddy; Silm Oktapani, Silm (EKSEKUSI, 2024)
ABSTRACTArticle 74 paragraph (2) letter b of Law Number 22 of 2009 concerning Road Traffic and Transportation, regulates the deletion of registration and identification of motorized vehicles by the police if the motorized vehicle owner does not re-register at least 2 years after the validity period expires. Vehicle Registration.". The aim of the research is to analyze the implementation of its elimination; to analyze the factors that hinder its implementation; To analyze efforts to overcome obstacles. Research methods are sociological legal research, statutory and case approaches; the research location is the Riau Regional Police; population and sample of relevant sources; data sources are primary, secondary and tertiary; Data collection techniques are observation, structured interviews and document/library study; qualitative data analysis with conclusions: inductive.  The results of the research are that the implementation of the elimination has not been carried out by the Riau Regional Police Traffic Directorate Sub-Directorate for four-wheeled motorized vehicles from 2021 to 2023. Factors that hinder its implementation are legal/legislative factors, law enforcement/government factors, facilities/facilities factors. As well as community factors. Efforts to overcome these obstacles include changes to existing regulations; Pekanbaru City DPRD forms Regional Regulations; The Regional Police Traffic Directorate Sub-Directorate of Riau carries out the removal with full commitment and responsibility in accordance with legal provisions; The Regident Sub-Directorate of the Riau Police Traffic Directorate has back up data on the registration and identification of motorized vehicles that have been deleted; additional competent personnel specifically for registration and identification of motorized vehicles; Negotiating with local governments to sort out bleaching policies; collaborating with the regional government to create a special team to implement the deletion of registration and identification of motorized vehicles; carry out legal outreach to the community and stake holders; Increased cooperation and coordination to work in an integrated manner; there must be a special budget to meet facilities and equipment; making banners at motor vehicle registration and identification service centers; The community is cooperative;  collaborating with Pekanbaru City community leaders to approach the community;  the whitening policy remains in place so that people can complete tax payments that are in arrears; involving the Pekanbaru City community in sustainable Community Traffic Education activities.Keywords: Removal, Regident; Pekanbaru ABSTRAKPasal 74 ayat (2) huruf b Undang-Undang Nomor 22 Tahun 2009 tentang Lalu Lintas dan Angkutan Jalan, mengatur adnya Penghapusan registrasi dan identifikasi kendaraan bermotor oleh oleh kepolisian jika pemilik Kendaraan Bermotor tidak melakukan registrasi ulang sekurang-kurangnya 2 tahun setelah habis masa berlaku STNK.”. Tujuan penelitian ialah Untuk menganalisis implementasi penhapusannya; untuk menganalisis faktor yang menghampat implementasinya; Untuk menganalisis upaya mengatasi hambatannya Metode penelitiaan yaitu penelitian hukum sosiologis, pendekatan perundang–undangan dan kasus; lokasi penelitian yaitu Polda Riau; populasi dan sampel dari narasumber–narasumber relevan; sumber data ialah primer, sekunder dan tersier; teknik pengumpulan data ialah observasi, wawancara terstruktur dan studi dokumen/kepustakaan; analisis datanya kualitatif dengan kesimpulan: induktif.  Hasil penelitian yaitu Implementasi penghapusan tersebut belum dilaksanakan Subdit Regident Ditlantas Polda Riau terhadap kendaraan bermotor roda empat pada tahun 2021 sampai 2023. Faktor  yang menghambat dalam implementasinya ialah Faktor hukum/ perundang-undanganl, Faktor penegak hukum/pemerintah, Faktor sarana/fasilitas. Serta Faktor masyarakat. Upaya mengatasi hambatan tersebut ialah dilakukan perubahan terhadap regulasi yang ada; DPRD Kota Pekanbaru membentuk Peraturan Daerah; Subdit Regident Ditlantas Polda Riau umelaksanakan penghapusan dengan penuh komitmen dan tanggung jawab sesuai dengan ketentuan hukum; Subdit Regident Ditlantas Polda Riau memiliki bac up data terhadap registrasi dan identifikasi kendaraan bermotor yang telah dihapus; penambahan personil yang berkompeten khusus Registrasi dan Identifikasi kendaraan bermotor; Melakukan negosiasi dengan pemerintah daerah untuk pemilahan kebijakan pemutihan; menggandeng pemerintah daerah membuat tim khusus pelaksanaan penghapusan registrasi dan identifikasi kendaraan bermotor tersebut; melakukan sosialiasai hukum kepada masyarakat dan stake holder; Peningkatan kerjasama dan koordinasi supaya bekerja secara terpadu; harus ada anggaran khusus untuk memenuhi sarana dan fasilitas; membuat banner-banner di pusat-pusat pelayanan registrasi dan identifikasi kendaraan bermotor; Masyarakat bersikap koperatif;  menggandeng tokoh masyarakat Kota Pekanbaru untuk melakukan pendekatan kepada masyarakat;  kebijakan pemutihan  tetap ada supaya masyarakat bisa menyelesaikan pembayaran pajak yang sudah tertunggak; melibatkan masyarakat Kota Pekanbaru dalam kegiatan Pendidikan Masyarakat Lalu Lintas secara berkelanjutan.Kata Kunci: Penghapusan,  Regident, Pekanbaru